2020
DOI: 10.1101/2020.01.27.920108
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Widespread conservation and lineage-specific diversification of genome-wide DNA methylation patterns across arthropods

Abstract: Cytosine methylation is an ancient epigenetic modification yet its function and extent within genomes is highly variable across eukaryotes. In mammals, methylation controls transposable elements and regulates the promoters of genes. In insects, DNA methylation is generally restricted to a small subset of transcribed genes, with both intergenic regions and transposable elements (TEs) depleted of methylation. The evolutionary origin and the function of these methylation patterns are poorly understood. Here we ch… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(78 citation statements)
references
References 66 publications
15
63
0
Order By: Relevance
“…vitripennis (Wang et al 2013). Moreover, CG methylation in B. germanica tends to concentrate towards the 3' region of the gene, in line with general DNA methylation trends in insects (Bewick et al 2017;Lewis et al 2020). In holometabolan species, DNA methylation appears to be biased towards the exons close to the 5' region of the gene (Bonasio et al 2012;Hunt et al 2013;Wang et al 2013;Glastad et al 2016), while in hemimetabolans it presents higher levels towards the 3' region of the gene coding part (Glastad et al 2016;Bewick et al 2019).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…vitripennis (Wang et al 2013). Moreover, CG methylation in B. germanica tends to concentrate towards the 3' region of the gene, in line with general DNA methylation trends in insects (Bewick et al 2017;Lewis et al 2020). In holometabolan species, DNA methylation appears to be biased towards the exons close to the 5' region of the gene (Bonasio et al 2012;Hunt et al 2013;Wang et al 2013;Glastad et al 2016), while in hemimetabolans it presents higher levels towards the 3' region of the gene coding part (Glastad et al 2016;Bewick et al 2019).…”
Section: Discussionsupporting
confidence: 55%
“…In general, our findings in embryos are similar to those observed by Bewick et al (2019) in B. germanica adults, using whole-genome bisulfite sequencing data. These authors found similar general levels of CG methylation, with the highest being observed in intragenic regions rather than intergenic regions, and which tended to concentrate towards the 3' UTR (Bewick et al 2019;Lewis et al 2020).…”
Section: Discussionmentioning
confidence: 71%
“…Where it has been studied, for example in Drosophila melanogaster, loss of function of DNMT2 is not associated with any severe developmental issues or lethality (Goll, et al 2006). Additionally, DNMT2-only insects like fruit flies and other holometabolous insects exhibit very low to no CpG methylation across their genome, in line with DNMT2's lack of DNA MTase activity (Lewis, et al 2020). Recent studies suggest that DNMT2 is a part of the cellular stress response that also acts against external stressors like pathogen challenges.…”
Section: Discussionmentioning
confidence: 98%
“…Consistent with DNMT2's role as a bona fide RNA MTase, evidence of genome-wide CpG methylation is nearly absent in these insects, leaving the biological role of this MTase unclear (Takayama, et al 2014;Lewis, et al 2020). Past studies investigating the biological function of DNMT2 suggest that it functions as a predominantly cytoplasmic protein during cellular stress, which can lead to increased longevity and greater host survival under stress conditions (Lin, et al 2005;.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation